Triphala: The Thai traditional herbal formulation for cancer treatment - Ariyaphong Wongnoppavich (2018)
Nowadays, Thai herbal plants are widely accepted in alternative medicine for treatment patients suffering deleterious diseases such as cancer. Having a variety of indications, several herbal formulas including Triphala have been routinely used as health tonic in Thai traditional and Ayurvedic medicines. The formulation of Triphala is a mixture of fruits of three plants: Phyllanthus emblica Linn., Terminalia chebula Retz. and Terminalia bellerica (Gaertn.) Roxb., all of which were reported to inhibit the growth and induce the death of cancer cells effectively. Therefore, anticancer activities inevitably turn out to be one of the essential properties of Triphala formula as well. It is likely that a number of active compounds in the formula, especially tannins, are the key agents that induce the apoptotic cell death via free radical production in cancer cells. On the other hand, all three fruits of these plants also contain high levels of antioxidants, capable of protecting normal cells from any free radical-mediated injuries effectively. Thus, the paradoxical role of Triphala is cell-type specific and becomes an advantage for usage of this formulation. Furthermore, Triphala has high potentials for inhibition and prevention of mutagenesis and metastasis of cancer cells. Finally, studies in the mechanism of action of Triphala and the product development as well as safety evaluation of the standard herbal extract are definitely required for future pharmacological applications of Triphala as anticancer agents for cancer therapy.